Motor-cognitive analysis of dual task walking in chronic obstructive pulmonary disease patients: An observational study using functional near infrared spectroscopy - Ahmed S. Hassan; Leandro Viçosa Bonetti; Manjiri Kulkarni; Dmitry Rozenberg; W. Darlene Reid (PLoS ONE, 2025)
Chronic Obstructive Pulmonary Disease (COPD), characterized by airflow limitation, commonly manifests cognitive and physical impairments that are often managed separately. The aim of this paper was to describe a dual task protocol of walking with a cognitive task to assess related decrements and associated ΔO 2 Hb in patients with COPD and older adults. Sample data illustrates responses from two individuals. Two single tasks and a dual task were applied in random order: (1) single task walking evaluated by the Zeno Electronic Walkway to measure gait speed; (2) a cognitive task of determining the number of 5-letter words accurately spelled backwards; (3) dual task walking combined with spelling words backwards. The decrements of performance were evaluated by examining the differences from single to dual task performance for two participants, to illustrate the methodology, as well as normalizing the decrement to the single task performance by the following equation:.